Work–Life and Well-Being in U.K. Therapeutic Prison Officers: A Thematic Analysis. (October 2018) - Walker, Emma J.; Egan, Helen H.; Jackson, Craig A.; Tonkin, Matthew
Previous research has clearly demonstrated the positive impact of therapeutic interventions on offenders' well-being. Much less is known about the impact on prison staff facilitating and delivering such interventions. We employed qualitative methodology to capture a deeper understanding of the work of therapeutic prison officers. Seven prison officers working in a U.K. Category B therapeutic community prison were interviewed about their working lives, including their own participation in therapy. Following a thematic analysis approach, key findings indicated that the physical and cultural work environment was very important to staff; the therapeutic element of their job role, although demanding, was both satisfying and rewarding; and that working in a therapeutic prison environment provided the opportunity for personal as well as professional development. We conclude that further attention should be given to the unique nature of therapeutic prison work and the positive impact it can have on well-being at work.